FAKTOR-FAKTOR MOTIVASI REMAJA BERWIRAUSAHA MELALUI BISNIS ONLINE DI BATUAMPAR PELAIHARI - Akhmad Samhudi; Siti Rizki Pardani (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
The number of conveniences in shopping online and the various types of products and services offered, make the Indonesian people make Online Shops as one of the new "shopping places" besides shopping centers.This study aims to determine and prove the motivational factors of Batu Ampar Pelaihari teenagers in entrepreneurship through online business.This type of research is descriptive quantitative. The data studied in this study were sourced from primary data and secondary data. The number of respondents who were used as observations in this study amounted to 40 people. Statistical analysis using simple linear, with testing tools using SPSS software version 20.00The results show that motivational factors can influence adolescent entrepreneurship in Batu Ampar Pelaihari. Variable data which is a simple conceptual path where motivation (X) / independent variable and entrepreneurial (Y) / dependent variable.The independent variable has a unidirectional relationship with the dependent variable because the independent variable has a positive coefficient, meaning that if the x variable increases, the y Variable also increases and vice versa.